Correlations of post-implant regional dosimetric parameters at 24 hours and one month, with clinical results of low-dose-rate brachytherapy for localized prostate cancer - Okazaki, Eiichiro; Kuratsukuri, Katsuyuki; Ishii, Kentaro; Tanaka, Tomoaki; Ogino, Ryo; Nishikawa, Tomohiro; Morimoto, Hideyuki; Hosono, Masako; Miki, Yukio (Journal of Contemporary Brachytherapy, 2017)
Purpose : To evaluate the correlations of post-implant regional dosimetrics at 24 hours (24 h) and 1 month after implant procedures, with clinical outcomes of low-dose-rate (LDR) brachytherapy for localized prostate cancer. Material and methods : Between January 2008 and December 2014, 130 consecutive patients treated for localized prostate cancer, receiving definitive iodine-125 ( 125 I) brachytherapy treatment were retrospectively analyzed. All patients underwent post-implant CT imaging for dosimetric analysis at 24 h and 1 month after implantation procedure. Prostate contours were divided into quadrants: anterior-superior (ASQ), posterior-superior (PSQ), anterior-inferior (AIQ), and posterior-inferior (PIQ). Predictive factors and cut-off values of biochemical failure-free survival (BFFS) and toxicities of LDR brachytherapy were analyzed. Results : The median follow-up time was 69.5 months. Seven patients (5.4%) had biochemical failure. The 3-year and 5-year BFFS rates were 96.7% and 93.1%, respectively. On multivariate analysis, prostate-specific antigen and Gleason score were significant prognostic factors for biochemical failure. D 90 (the minimal dose received by 90% of the volume) of PSQ and PIQ at 24 h, and D 90 of PSQ at 1 month were also significant factors. The cut-off values of PSQ D 90 were 145 Gy at 24 h and 160 Gy at 1 month. D 90 of the whole prostate was not significant at 24 h and at 1 month. D 90 of PSQ at 1 month was a significant factor for rectal hemorrhage. Conclusions : Post-implant D 90 of PSQ is significantly associated with BFFS for localized prostate cancer not only at 1 month, but also at 24 hours. D 90 of PSQ at 1 month is also a significant factor for rectal hemorrhage.